Investigating creative problem-solving in learning mathematics through cyclical action research - Ibrahim, Hasniza; Isa, Norshahira; Embong, Zulmaryan (Academic Inspired Network (AIN), 2023)
We owe much of today's technological advances to the creativity of scientists and mathematicians. We marvel at the ability of those who can invent or come up with something novel and innovative for the progress of their country. Not surprisingly, creativity is a trait that a country yearns for in its citizens. The main objective of this research is to study the effects of Form One students' mathematical performance after the implementation of teaching through creative problem-solving (CPS) approaches. The other objective is to examine the level of students' creative problem-solving ability during the interventions. A class of 24 students from Gombak, Selangor, was selected using purposive sampling for this cyclical action research (CAR) design study. Before and after going through the three cycles of the interventions, all of the students were assessed using mathematics items (pre-test and post-test). During the interventions, the students were observed using an observation creativity checklist (quantitative approach) and semi-structured observation (qualitative approach). However, this article will only present the findings based on the observation checklist. The results on mathematics items showed that 50% of the participants had improved after the interventions, and the Average Mean Score for all students increased by 27%. The male participants improved better (89%) in mathematics item tests than the female participants (23%). Meanwhile, the results from the observation checklist showed that the average mean scores in all 4 components of creativity (Originality, Elaboration, Fluency and Flexibility) showed an increasing trend from moderate to high levels. The mean scores are as follows; M=3.07 (SD=0.64), M=3.14 (SD=0.77) and M=3.69 (SD=0.77) for Cycle 1, Cycle 2, and Cycle 3, respectively.